2015
DOI: 10.1039/c5mt00052a
|View full text |Cite
|
Sign up to set email alerts
|

Loss of pdr-1/parkin influences Mn homeostasis through altered ferroportin expression in C. elegans

Abstract: Overexposure to the essential metal manganese (Mn) can result in an irreversible condition known as manganism that shares similar pathophysiology with Parkinson's disease (PD), including dopaminergic (DAergic) cell loss that leads to motor and cognitive impairments. However, the mechanisms behind this neurotoxicity and its relationship with PD remain unclear. Many genes confer risk for autosomal recessive, early-onset PD, including the parkin/PARK2 gene that encodes for the E3 ubiquitin ligase Parkin. Using Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 60 publications
(129 reference statements)
1
17
0
Order By: Relevance
“…Hence, we hypothesized that the absence of hsp-70 would alter the expression of these genes. First, we verified for the first time that Mn increases mRNA levels of all these genes in wild type worms, which is in agreement with the hypothesis that these proteins are required to protect cells against Mn-induced toxicity [19, 20, 41]. While in the hsp-70 mutants mRNA levels of pdr-1 and djr-1.1 increased dose-dependently in a manner indistinguishable from N2 worms, the pink1 expression failed to increase and was not significantly different compared to non-treated mutants.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Hence, we hypothesized that the absence of hsp-70 would alter the expression of these genes. First, we verified for the first time that Mn increases mRNA levels of all these genes in wild type worms, which is in agreement with the hypothesis that these proteins are required to protect cells against Mn-induced toxicity [19, 20, 41]. While in the hsp-70 mutants mRNA levels of pdr-1 and djr-1.1 increased dose-dependently in a manner indistinguishable from N2 worms, the pink1 expression failed to increase and was not significantly different compared to non-treated mutants.…”
Section: Discussionsupporting
confidence: 82%
“…Recently, our group demonstrated that pdr-1 and djr-1.1 loss in C. elegans increased their susceptibility to Mn in comparison to wild type worms and that the observed enhanced oxidative stress is related to increased Mn accumulation [19]. In addition, the higher Mn accumulation caused by loss of pdr-1/parkin gene was due to reduction of ferroportin (a Mn cell exporter) expression in worms [20]. Furthermore, Chen et al demonstrated that worms overexpressing DJR-1.2 are not subject to lifespan reduction caused by Mn exposure, in contrary to djr-1.2 mutants [41].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these behaviors, basal slowing response is DA-specific, and other behaviors are usually controlled by DA along with other neurotransmitters, such as serotonin, glutamate or GABA, etc. To date, basal slowing response and dauer movement have been studied with Mn exposure [175, 177, 178]. Levya-Illades, Chen et al (2014), have shown that Mn exposure resulted in decreased basal slowing response, while expression of Mn exporter SLC30A10 exclusively in DAergic neurons rescued this behavioral defect together with decreased DAergic neurodegeneration [67].…”
Section: Main Textmentioning
confidence: 99%
“…Total RNA was isolated using the Trizol method as described before50. Briefly 1 mL Trizol (Life Technologies) was added to each tube containing about 60 000 eggs, 20 000 L1 stage or 4 000 L4 stage worms, followed by three cycles of freezing in liquid nitrogen and thawing.…”
Section: Methodsmentioning
confidence: 99%